2014
DOI: 10.17503/agrivita-2014-36-2-p120-127
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Arthropods on Cocoa Plantation in Three Strata of Shade Tree

Abstract: The Research was aimed to identify the diversity of arthropods in Cocoa plantation in three strata of shade tree. Research was conducted in Rahmat village, the sub-district of Palolo, District of Sigi, the Province of Central Sulawesi, Indonesia from December 2012 to June 2013.Berlese funnel, Pitfall, Malaise and Light trap were used to collect arthropod samples. There were five indices such as species richness (R), species evenness (E), species diversity (H`and D), and species similarity (Iss) to analyze the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Soil arthropods generally prefer moist and shade habitats. This was supported by many studies such as reported that trees shaded affected the number of species [3]. Species richness is highest in habitat with two strata of shade canopy trees, hence inhibit of light penetration.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…Soil arthropods generally prefer moist and shade habitats. This was supported by many studies such as reported that trees shaded affected the number of species [3]. Species richness is highest in habitat with two strata of shade canopy trees, hence inhibit of light penetration.…”
Section: Resultsmentioning
confidence: 57%
“…Concerns about the responses of soil arthropods to the human activities such as cultivation, urbanization and silvi-culture practice have been reported in several studies [1,2,3,4]. Habitat destruction and fragmentation, introduced species and deforestation are major human activities in the tropical region.…”
Section: Introductionmentioning
confidence: 99%
“…Shannon and Pielou index across different land use type using pitfall technique ranged between 0.43 (apple guava) to 2.7 (native forest) and 0.11 (apple guava) to 0.86 (tomato), respectively (Siquera et al, 2014), which lower than the value of H and E in this study (Table 4). (Toana at al., 2014). The result showed that species richness (R) of arthropods under the two strata of shade tree, species evenness (E) and both of species diversity indices Shannon (H`) and Simpson (D) were the highest at the value of 18.21, 0.83, 4.3, and 0.83 respectively, followed by one stratum of shade tree and without shade tree as the lowest.…”
Section: Resultsmentioning
confidence: 99%
“…Greater plant diversity may also enhance soil quality, further supporting agricultural productivity in nutrient-limited tropical systems (Sistla et al, 2016). One of well know typical agroforestry system is involving selected economic tree species such cocoa (Toana et al, 2014) or coffee) under canopies of other trees such as Pines, Albizia or Mahogany (Verbist, 2005;Evisal et al, 2016). Toana et al (2014) who reviewed this system in improving biodiversity reported that in cocoa plantation at Central Sulawesi, under two strata of shade tree, Species Richness (R), Species Evenness (E), Shannon and Simpson index were the highest with value of 18.216, 0.839, 4.383 and 0.833 respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation